Fair payment and just benefits to enhance diversity in clinical research. Issue 1 (14th July 2021) - Bierer, Barbara E.; White, Sarah A.; Gelinas, Luke; Strauss, David H.
Abstract: Routine, nonmedical and ancillary medical costs associated with participation in clinical research create barriers to enrollment for economically disadvantaged individuals. To the extent that race, ethnicity, and gender are linked to SES, such barriers impact efforts to diversify clinical research enrollment. But payment policies and practices often reflect the longstanding and singular concern that payment to participants will bias decision-making and compromise informed consent. We argue that this concern must be viewed in a larger ethical context in which the untoward consequences for the individual participant and for the broader research enterprise are considerable when either inadequate or no payment is provided for expenses incurred ("reimbursement") and time committed ("compensation"). Fairness in payment and protection from undue influence of payment on the informed consent process are important but distinct ethical considerations. Fundamentally, approaches to payment that leave participants financially worse off as a consequence of taking part in research are inherently unjust as they have a differential impact on recruitment and retention based on socioeconomic status. Sponsors, funders, investigators, and IRBs must be cognizant of the impact of inadequate payment on clinical trial inclusion of historically understudied groups. We address practical and fair payment strategies to advance inclusion, the additional barrier of ancillary medical costs, and potential unintended consequences of payment.